Efficacy of a Eucalyptus oil-based dentifrice in reducing plaque and gingival bleeding scores - A randomized clinical crossover study - Fatema Alzahraa Osman; Leen Abdulghani Sarhan; Nirmeen Elhussein Eladl; Vijay Desai; Jayaraj Narayanan; Lakshmi Thangavelu; Sudhir Rama Varma (Wolters Kluwer Medknow Publications, 2024)
Herbal products in dentistry have grown significantly. In the current scenario, herbal products are believed to be an effective adjunct to other medications. The present study aims to evaluate Eucalyptus oil and miswak (Salvadora persica) toothpaste for its efficacy in observable reduction in plaque and gingival bleeding. Sixty participants with gingivitis were enrolled in the present study. The study included an interim period (washout) comparing miswak and Eucalyptus toothpaste. Plaque scores were measured at designated time intervals. Both herbal toothpastes significantly decreased plaque index. Nevertheless, with relation to miswak (P = 0.002), Eucalyptus oil-based toothpaste exhibited reduction in bleeding scores. When participants were asked to return to their routine toothpaste, no changes were observed. Results from the study showed that the toothpaste containing Eucalyptus showed a significant decrease in gingival bleeding. More investigations should be looked on the medicinal applications of Eucalyptus toothpaste on commonly seen periodontal parameters.